The Role of PJA2-CDK5R1 in β-cell Function - Mohamud, Yasir (Université d'Ottawa / University of Ottawa, 2015)
Diabetes is a global epidemic characterized by an inability to control blood glucose due to lack of insulin secretion and/or regulation. The International Diabetes Federation (IDF) estimates approximately 382 million people worldwide to be affected by diabetes and domestically, the Canadian Diabetes Association estimates approximately 9 million diabetic/pre-diabetics. The protein Cdk5r1/p35 negatively regulates insulin secretion and thus can be targeted as a novel therapy for diabetes. Immunoprecipitation coupled with mass spectrometry has identified candidate interactors of p35. Using high throughput RNAi screening, candidate genes were knocked down with target shRNA and p35 protein levels were monitored. The screen identified RPAP3 as a potential regulator of p35 levels. Knockdown of RPAP3 increased p35 protein levels however insulin secretion was unaffected suggesting a more complex model. In the same manner, PJA2 was identified as the E3 ligase responsible for p35 ubiquitination and subsequent degradation. With the preface that PJA2 undergoes auto-ubiquitination, site-directed mutagenesis was employed to generate lysine to arginine mutants in an effort to identify auto-ubiquitination sites. Mutating lysines K642, K657, and K666 (K3R) causes PJA2 stabilization and reduced auto-ubiquitination compared to wild-type. In vitro ubiquitination assays demonstrate that K3R is functional and can ubiquitinate GST-p35. However, overexpression of PJA2 in Min6 cells is associated with poor regulation of insulin secretion. Co-immunoprecipitation experiments reveal that PJA2 undergoes self-interaction. PJA2-p35 interaction is further characterized by demonstrating that p25 is sufficient to interact with PJA2. Furthermore, PJA2-p35 dynamics may affect PJA2 auto-ubiquitination capacity.